Insights into the medicinal chemistry of heterocycles integrated with a pyrazolo[1, 5-a]pyrimidine scaffold. Issue 10 (8th September 2022) - Hammouda, Mohamed M.; Gaffer, Hatem E.; Elattar, Khaled M.
Abstract : Pyrazolopyrimidine core is the basic skeleton of many drugs with privileged biological profiles. In this study, the biological characteristics, and samples of synthetic approaches and reactivity of pyrazolo[1, 5- a ]pyrimidines were highlighted. Abstract : Pyrazolo[1, 5- a ]pyrimidines are the dominant motif of many drugs; for instance, zaleplon and indiplon are sedative agents and ocinaplon was identified as an anxiolytic agent. The importance of this class of compounds lies in its varied and significant biological activities, and accordingly, considerable methods have been devised to prepare these compounds. Hence, other derivatives of this class of compounds were prepared by substitution reactions with different nucleophiles exploiting the activity of groups linked to the ring carbon and nitrogen atoms. The methods used vary through the condensation reactions of the aminopyrazoles with 1, 2-allenic, enaminonitriles, enaminones, 1, 3-diketones, unsaturated nitriles, or unsaturated ketones. Alternatively, these compounds are prepared through the reactions of acyclic reagents, as these methods were recently developed efficiently with high yields. The current review highlighted the recent progress of the therapeutic potential of pyrazolo[1, 5- a ]pyrimidines as antimicrobial, anticancer, antianxiety, anti-proliferative, analgesic, and antioxidant agents, carboxylesterase, translocator protein and PDE10A inhibitors, and selective kinase inhibitors.